CLIMATIC FACTORS OF THE FORMATION OF THE GEOSYSTEMS OF THE UPPER ERTIS BASIN - N.Қ. Қabdrakhmanova,; M.N. Musabaeva,; N.ZH. Zhensikbaeva, (Academic Journal of Physical and Chemical Sciences, 2019)
According to the authors, due to the large distance and isolation of mountain systems, warm and moist air masses from the Atlantic Ocean reach here transformed, having lost most of the moisture, and air masses penetrating from the Arctic Ocean are cold and dry. Hilly low-slope and flat areas of the Ertis left bank are especially dry. The highest moisture content is characteristic of the western and northern peripheral as well as central highland regions of Altai. Complex orography, the presence of closed basins and plateaus cause large differences in the climatic features of individual regions of Altai. The climate of Altai as a whole is much milder than in the neighboring areas, the summer is cool, and the winter is relatively warmer.